2004
DOI: 10.1002/hep.20286
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the leukocyte cell-derived chemotaxin 2 as a direct target gene of β-catenin in the liver

Abstract: To clarify molecular mechanisms underlying liver carcinogenesis induced by aberrant activation of Wnt pathway, we isolated the target genes of ␤-catenin from mice exhibiting constitutive activated ␤-catenin in the liver. Adenovirus-mediated expression of oncogenic ␤-catenin was used to isolate early targets of ␤-catenin in the liver. Suppression subtractive hybridization was used to identify the leukocyte cell-derived chemotaxin 2 (LECT2) gene as a direct target of ␤-catenin. Northern blot and immunohistochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
113
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 108 publications
(123 citation statements)
references
References 28 publications
8
113
0
2
Order By: Relevance
“…We demonstrated that among the various liver b-catenin target genes tested (Cadoret et al, 2002;Yamamoto et al, 2003;Colnot et al, 2004;Ovejero et al, 2004), three were good markers of active b-catenin signaling: GS, GPR49 and GLT-1. Immunohistochemical analyses showed that GS is a marker of b-catenin activation in human HCC.…”
mentioning
confidence: 93%
See 3 more Smart Citations
“…We demonstrated that among the various liver b-catenin target genes tested (Cadoret et al, 2002;Yamamoto et al, 2003;Colnot et al, 2004;Ovejero et al, 2004), three were good markers of active b-catenin signaling: GS, GPR49 and GLT-1. Immunohistochemical analyses showed that GS is a marker of b-catenin activation in human HCC.…”
mentioning
confidence: 93%
“…Control non-mutated HCC cell lines did not have mutations in either b-catenin or Axin1 (Table 1). The seven b-catenin target genes included two canonical b-catenin target genes, c-myc and cyclinD1 (He et al, 1998;Tetsu and McCormick, 1999), and five recently identified b-catenin target genes overexpressed in human HCCs: glutamine synthetase (GS) (also known as GLUL1), the glutamate transporter (GLT)-1, ornithine aminotransferase (OAT) (Cadoret et al, 2002), an orphan G-protein-coupled receptor (GPR)49 (also known as LGR5) (Yamamoto et al, 2003) and a chemokine-like protein LECT2 (Ovejero et al, 2004). We assayed mRNA of these seven b-catenin target genes in 45 HCCs and in 21 of the matched non-tumor liver tissues (Figure 1).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…La voie de signalisation Wnt/-caténine est constitutivement activée dans 30 à 40 % des CHC chez l'homme [3,8]. Récemment, nous avons identifié une cible moléculaire contrôlée par la -caténine appelée LECT2 pour leukocyte cell-derived chemotaxin 2 [10]. On connaît encore très peu les fonctions de LECT2, bien qu'un rôle immunomodulateur lui ait été attribué.…”
Section: Le Carcinome Hépatocellulaire (Chc)unclassified